Digital Pulley Reconstruction Using Pulley Allografts: A Comparison With Traditional Tendon-Based Techniques. (June 2019) - Martinez, Roberto A.; Liston, Jared; Archual, Anthony J.; Gui, Jane; Drake, David B.; DeGeorge, Brent R.
Abstract : Background: The safety and feasibility of sterile, acellular pulley allografts in reconstruction has been previously demonstrated. Comparisons with tendon-based techniques for pulley reconstruction have not been reported. We hypothesized that the use of allograft pulleys would result in reduced procedural time and equivalent clinical outcomes as compared with traditional tendon-based reconstructive techniques. Methods: All cases of pulley reconstruction using either allograft pulleys or tendon-based pulley reconstruction between November 2013 and November 2015 were reviewed. Patients who underwent concomitant procedures were excluded. Patient demographics, comorbidities, operative details (tourniquet and total operative times, number of pulleys repaired), postoperative complications (surgical site infection, reoperation, stiffness, and persistent pain), disability of the arm, shoulder and hand scores, and follow-up data were recorded. A P value of <0.05 was considered significant. Results: Fifteen pulleys in 10 patients were reconstructed: 5 tendon-based and 5 with allograft. Average length of follow-up was 12.5 ± 2.9 months. There was no difference in patient demographic factors or comorbidities between groups. The most common indication for surgery was trauma. Four of 5 patients in the allograft group had multiple pulleys reconstructed versus 1 in the tendon-based group. One patient in the tendon-based group required reoperation versus 0 in the allograft group. Total operative and tourniquet times were significantly reduced in the allograft group (46 ± 5.5 vs 89 ± 12.9 minutes and 34 ± 6.8 vs 63 ± 5.3 minutes; P = 0.015 and 0.014). Postoperative disability of the arm, shoulder and hand scores were lower in the allograft group (56.8 vs 3.6, P = 0.11). There was no significant difference in postoperative range of motion between groups. Conclusion: Pulley reconstruction with allograft is an efficient, technically feasible, reconstructive technique that adheres to the principle of replacing like with like, while eliminating donor site morbidity. Overall operative and tourniquet times were significantly shorter using allograft pulleys for pulley reconstruction.